Leveraging Digitalization in Healthcare Systems: It’s Impact on Quality of Care - S. Nithya Priya; A. Bhoomadevi; Archana Koul; Dr Shyamkumar Sriram (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction:The rapid transformation of healthcare systems worldwide through digitalization presents unparalleled opportunities to advance patient care, increase operational efficiency, and foster innovation in patient care. Methods:This study analysed the impact of digitalization on quality on care in a private multi-speciality hospital. Methodology adopted in the study was descriptive study and stratified random sampling technique is used for data collection.The study analysed the relationship between demographic factors (age, marital status, gender, and experience) and their effects on digitalization and quality of care. Statistic tools like correlation, regression was used to test the hypothesis. Results:It was observed from correlation that the factors of digitalization and quality of care has strong and positive correlation. The regression analysis found that integrating data through digitalization factors significantly (p < 0.01) improved quality of care, even when controlling for other variables. Conclusion:The research underscores the significant role of digitalization in improving the quality of patient care within a private multi-specialty hospital. The strong correlation and regression analysis results demonstrate that the integration of digital technologies can positively impact various aspects of healthcare delivery. By leveraging digital tools and data-driven insights, healthcare providers can optimize processes, enhance patient experiences, and ultimately improve overall patient outcomes. The study’s findings highlight the potential benefits of embracing digitalization as a key driver for quality improvement in healthcare settings.